Dialectology of the Montenegrin Language - Čirgić, Adnan (Studies in Slavic, Baltic, and Eastern European Languages and Cultures, 2020)
This book brings a new methodological framework for classification of Montenegrin dialects, introducing new criteria to it and focusing on the isoglosses which make those dialects compact. The book is based on field research published in the past 150 years.